Physical Activity in Pregnancy and Its Role in Blood Pressure Control and the Prevention of Hypertensive Disorders of Pregnancy: A Narrative Review - Podolska, Anna; Paluchowicz, Karolina; Siwicka, Katarzyna; Szewczyk, Konrad; Janasik, Laura; Kociucka, Patrycja; Sadowski, Krzysztof; Modelska, Julia; Jeleń, Anita (Journal of Education, Health and Sport, 2026)
Background. Hypertensive disorders of pregnancy (HDP), including gestational hypertension and preeclampsia, are among the most common and serious obstetric complications worldwide. They result from impaired cardiovascular adaptation to pregnancy and significantly increase maternal and perinatal morbidity and mortality. Physical activity is considered a safe, non-pharmacological intervention with potential preventive benefits. Aim. To summarize current evidence on the impact of physical activity during pregnancy on blood pressure regulation and the risk of HDP. Material and Methods. This narrative review included publications indexed in PubMed and Google Scholar from 2020–2026. Observational and interventional studies, systematic reviews, meta-analyses, and international guidelines assessing associations between physical activity, blood pressure, and HDP were analyzed. Articles published before 2020 (except key recommendations) and those not in English or Polish were excluded. Results. Pregnancy involves increased cardiac output, blood volume, and heart rate, with decreased systemic vascular resistance and blood pressure. Disruption of these adaptations predisposes women to HDP. Regular moderate-intensity physical activity improves endothelial function, reduces oxidative stress and inflammation, enhances autonomic balance and supports weight control. Evidence shows lower systolic and diastolic blood pressure and a reduced risk of gestational hypertension among physically active pregnant women. However, findings on preeclampsia prevention remain inconclusive, likely due to its multifactorial etiology. Conclusions. Moderate physical activity during pregnancy is a safe strategy that promotes cardiovascular adaptation, improves blood pressure control, and lowers the risk of HDP, particularly gestational hypertension. Although its role in preventing preeclampsia remains unclear, current evidence supports including physical activity in routine prenatal care.